PENGELOLAAN DAN PENGEMBANGAN BADAN USAHA MILIK DESA - Rahyunir Rauf (VALUTA, 2016)
Various notions of the village has been widely presented by experts from variousdisciplines, and each understanding about the village appeared to have their variousdifferences separate depending on what point of view or which approach is used byexperts in view, describe and judge about the village, such as in terms of sociology,administration, politics, policy standpoint and in terms of economics. The Reforms inIndonesia In 1998 has brought many changes in Indonesian villages, one with thepresence of village-owned enterprises (BUMDES) on Law Number 22 Year 1999 onRegional Government. The village has a variety of potential that can be developed forthe welfare of the local villagers. Therefore, the village is also expressed as groupsorganized nature that have objects of material and immaterial (geordnede groupen van eigen blijvend meth character bewind en eigen marericel vermogen). The village hasthe potential and richness which is set in accordance with the institutional systemdeveloped and maintained by the local villagers. So that a higher village relies on thestrength of the potential and the resources owned by the village itself through variousforms of participation of the village community itself, so without too attached anddependent on help from the elements such as local government agencies or other parties( companies) which have more give more assistance to the villagers themselves bothpersonally and institutionally from the village. In connection with the application of theconcept of autonomy of the village, it is necessary to strengthen efforts towards thevillage administration. Therefore, the village-owned enterprises need to be managedand developed properly by the village government, so BUMDES can be used as one ofthe potential that can be used as an indicator of economic improvement of thegovernment and villagers.